Demographic profile and prevalence of spontaneous abortion in the health macro-regions of the state of Paraná (Research, Society and Development, 2022)
Objective: to characterize the reported cases of spontaneous abortion and the prevalence in the state of Paraná, from 2017 to 2021. Methods: An exploratory descriptive study with a quantitative design was carried out with data obtained from the SUS Hospital Information System (SIH/SUS), made available by the Department of Informatics of the SUS (DATASUS). Results: In the period 2017 to 2021, in Paraná, the prevalence of reported spontaneous abortion was 14,095 cases. Among the 22 health macro-regions of the state. With the highest rate of spontaneous abortion was the 9th Regional Health (Foz Do Iguaçu) with 42.7/1000 live births and the 12th RS (Umuarama) with the lowest number of cases. The highest prevalence is observed in the age group from 20 to 24 years and in relation to race/color, women who considered themselves white predominated. Regarding the type of care, a greater number of urgent care than elective care was highlighted. In addition, the costs of this type of care were proportional to the cases attended per year, however, there were six cases of maternal mortality resulting from complications of spontaneous abortion Conclusion: We observed a reduction in cases of spontaneous abortion in the state of Paraná in the last five years. years, which may reflect underreporting due to the COVID-19 pandemic or improvement in primary health care, is associated with contraceptive use and health care and increased implementation of public policies in order to reduce health problems.